2016
DOI: 10.5152/tjbh.2016.2897
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Diffusion-weighted Imaging and Apparent Diffusion Coefficient Values in the Differentiation of Breast Lesions, Histpathologic Subgroups and Correlatıon with Prognostıc Factors using 3.0 Tesla MR

Abstract: IntroductionMagnetic resonance imaging (MRI) as a method for breast exams has been used increasingly frequently during the last decade. In particular, it is preferred for selected cases as a diagnostic and problem-solving method for its high contrast resolution, multiplanar capability of examination, lack of ionizing radiation, and capacity to obtain dynamic contrast images (1, 2). Conventional MRI has disadvantages such as time-consuming screening and requirement of high-value contrast agents (3). Despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
5
13
0
Order By: Relevance
“…Studies in different types of cancer have also proposed DW-MRI as a marker to distinguish benign and malignant tumors and to evaluate the aggressiveness of cancer based on ADC-values, but that goes beyond the scope of the present study [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different types of cancer have also proposed DW-MRI as a marker to distinguish benign and malignant tumors and to evaluate the aggressiveness of cancer based on ADC-values, but that goes beyond the scope of the present study [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the whole volume ADC histogram could supply more information and predict Ki-67 more accurately than a single ADC value. Some studies analysed the associations between the ADC value and the expression of Ki-67 in breast cancer [ 7 , 18 , 19 ] with different ROI placements; however, data about the relationships between the Ki-67 index and ADC value were inconsistent. Mori et al reported that there was a moderately significant correlation between the whole tumour ADC histogram (ADC-mean) and Ki-67 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Surov et al found only a weak negative correlation between these two parameters [ 18 ]. Some studies found that there were no statistically significant correlations between the ADC value and Ki-67 [ 7 , 19 ]. Overall, the possibility of using ADC as an imaging marker for proliferation activity in breast cancer is uncertain in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, Aydin et al could find only a weak negative correlation between ADC and Ki-67-values in BC ( r = − 0.279; p = 0.029) [ 10 ]. Finally, some authors did not identify statistically significant correlations between these parameters [ 11 – 13 ]. Similarly, data about relationships between tumor grade and ADC were also inconsistent.…”
Section: Introductionmentioning
confidence: 99%